1992
DOI: 10.1177/001316449205200121
|View full text |Cite
|
Sign up to set email alerts
|

Validity and Reliability of the Maslach Burnout Inventory for a Sample of Non-Western Teachers

Abstract: In order to assess the construct validity and reliability of the Maslach Burnout Inventory (MBI) in a Non-Western setting, the instrument was administered to 223 Jordanian teachers. Responses to the MBI were subjected to principal factors analysis. Three factors, rotated obliquely, accounted for 42% and 43% of the total variance of the frequency and intensity dimensions, respectively. The correlations between these two dimensions for each of the three subscales were rather large and ranged from .84 and .92. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
30
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 8 publications
5
30
1
Order By: Relevance
“…In conclusion, we can say that our scale, which has 4 components, has not only a good validity but also a great reliability. These findings are in line with the conducted studies of some researchers (16, 23-26) (1988), while inconsistent with others (19)(20)(21) due to the fact that they found a 2 factor structure.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…In conclusion, we can say that our scale, which has 4 components, has not only a good validity but also a great reliability. These findings are in line with the conducted studies of some researchers (16, 23-26) (1988), while inconsistent with others (19)(20)(21) due to the fact that they found a 2 factor structure.…”
Section: Discussionsupporting
confidence: 74%
“…The result clearly supported the 3 factors structure of burnout. Other studies have found a 2 factor structure (19)(20)(21)(22), while a 4 factor structure has been showed by other researchers (23)(24)(25)(26). According to these research results, it can be concluded that burnout is a complex phenomenon with a multi-factorial structure.…”
Section: Research and Theoretical Frameworkmentioning
confidence: 55%
“…In fact, Walkey and Green (1992; also see Green et al, 1991) found that depersonalization combined with emotional exhaustion to form what they viewed as the core of burnout. The study of teachers by Iwanicki and Schwab (1981) found depersonalization split into two factors which they classi®ed as job-related and student-related (also see Abu-Hilal and Salameh, 1992;Garden, 1987). , recommended further psychometric development of depersonalization and, therefore, the following proposition will be investigated:…”
Section: Introductionmentioning
confidence: 99%
“…On one hand, EFA has an inherent limitation in which the number of factors can be specified a priori, but the pattern of factor loadings cannot be controlled. Several other studies in which EFA has been employed have yielded a pattern of shifting items (e.g., Abu-Hilal & Salameh (1992). On the other hand, the shifting items occurred in the smallest sample.…”
Section: Exploratory Factor Analysismentioning
confidence: 88%